2019
DOI: 10.1016/j.ijhydene.2018.08.107
|View full text |Cite
|
Sign up to set email alerts
|

Thermal radiation from cryogenic hydrogen jet fires

Abstract: The thermal hazards from ignited under-expanded cryogenic releases are not yet fully understood and reliable predictive tools are missing. This study aims at validation of a CFD model to simulate flame length and radiative heat flux for cryogenic hydrogen jet fires. The simulation results are compared against the experimental data by Sandia National Laboratories on cryogenic hydrogen fires from storage with pressure up to 5 bar abs and temperature in the range 48-82 K. The release source is modelled using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…It was found that the change of turbulence intensity (TI) and turbulent length scale (TLS) from TI=30% and TLS=0.33Deff to TI=4% and TLS=0.07Deff has a considerable effect (up to 30% decrease) on the monitored radiative heat flux in the closest sensors at distances 1.0-1.5 m. The set of turbulence characteristics were defined according to a parametric study conducted at HySAFER on hydrogen concentration jet decay (TI=30%, TLS=0.33Deff) and experimental data on air under-expanded jets (TI=4% and TLS=0.07Deff) [26]. Minor effect of turbulent characteristics on radiative heat flux was found by the authors for steady state cryogenic jet fires where maximum variation was 15% [27]. This difference is presumed to be due to the different source modelling technique, as the volumetric source is more sensitive to the applied turbulence characteristics whereas they have minor effect for the constant diameter notional nozzle implementation with specified velocity at inflow boundary condition.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the change of turbulence intensity (TI) and turbulent length scale (TLS) from TI=30% and TLS=0.33Deff to TI=4% and TLS=0.07Deff has a considerable effect (up to 30% decrease) on the monitored radiative heat flux in the closest sensors at distances 1.0-1.5 m. The set of turbulence characteristics were defined according to a parametric study conducted at HySAFER on hydrogen concentration jet decay (TI=30%, TLS=0.33Deff) and experimental data on air under-expanded jets (TI=4% and TLS=0.07Deff) [26]. Minor effect of turbulent characteristics on radiative heat flux was found by the authors for steady state cryogenic jet fires where maximum variation was 15% [27]. This difference is presumed to be due to the different source modelling technique, as the volumetric source is more sensitive to the applied turbulence characteristics whereas they have minor effect for the constant diameter notional nozzle implementation with specified velocity at inflow boundary condition.…”
Section: Resultsmentioning
confidence: 99%
“…Since the product of hydrogen combustion is water vapour, the Exponential wide band (EWB) model, suggested by Yan et al [26] is used in this study. The model has been tested and validated against experimental results in previous work at Ulster [27]. The radiative transfer equation (RTE) was discretised by using 3 x 3 pixels and 5 x 5 angular divisions.…”
Section: Radiationmentioning
confidence: 99%
“…It is recommended that 5 x 5 divisions are a strong candidate to be used for the variation of temperature in space [28]. However, a previous study [27] investigated the effect of radiation model angular discretisation, and 12 x 12, 10 x 10, 7 x 7 and 5 x 5 angular discretisation were compared. For their geometry and simulation, 10 x 10 or above provided better results on the sensors to receive the radiation emitted by the flame along all its length.…”
Section: Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) Thermal imaging Propane Horizontal Correlated heat release rate based on jet flame Froude number experimentally. Cirrone et al. (2019a) CFD code.…”
Section: Introductionmentioning
confidence: 99%